An annotated checklist of parasitic lice (Insecta: Phthiraptera) from the Galápagos Islands - Palma, Ricardo L.; Peck, Stewart B. (Zootaxa, 2013)
We list all described species and subspecies of parasitic lice from theGalápagos Islands, based on literature and specimen records. A total of eight families, 47 genera, and 104 species and subspecies of parasitic lice are listed, of which 26 are new species records and eight are new genus records. Also, we report 17 new host-louse associations. The checklist includes 17 endemic species (16 from birds, one from a mammal), 79 native species and subspecies (78 from birds, one from a mammal), and eight species and subspecies (five from birds, three from mammals) introduced by human agency. Nine species assigned in error to theGalápagos Islandsin the literature are discussed and deleted from the fauna. For each valid species and subspecies we give information on its taxonomic history, type material, host associations, geographic distribution, biogeographical status, systematic relationships, and relevant literature references. We also give a brief summary of louse biology, and an account of the history of louse collecting, expeditions, collections, and research relating toGalápagos Islandslice. We include a host-parasite list, and a list of hosts which breed in theGalápagos Islandsbut without lice recorded from them. Also, we formally designate four lectotypes from the Kellogg Collection.